Peningkatan Minat Menabung di Bank Syariah melalui Program Office Channeling - Chotifah, Yuliana Siti (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Office channeling is one way to boost the growth of sharia banking industry significantly. Banks expect customers' knowledge of office channelling to increase the interest of customers in saving in a sharia bank. This study analyzed how far the influence of customer knowledge of office channeling to the interest of saving. The data is primary from interviewing to 100 customers BRI Kartasura whose savings by a questionnaire. The respondents chosen by random from total 43.985 customers till December 2016. Technique of analyzing the data used Simple Regression. The result of this research showed the Customer Knowledge to office channeling had a positive and significant effect on interest in saving in Sharia Bank. The research gives a contribution to (a) academician; as an evidence of theory, (b) Sharia Bank; good information to increase socialization to customers about office channeling.